2017
DOI: 10.1158/1541-7786.mcr-16-0447
|View full text |Cite
|
Sign up to set email alerts
|

Abituzumab Targeting of αV-Class Integrins Inhibits Prostate Cancer Progression

Abstract: Integrins that contain an integrin alpha V subunit contribute to multiple functions that promote cancer progression. The goal of this study was to determine if abituzumab (DI17E6, EMD 525797), a humanized monoclonal antibody (mAb) against integrin alpha V impacts, prostate cancer (PCa) progression. To evaluate this, PCa cells were treated with DI17E6 and its effects on proliferation, apoptosis, cell cycle, adhesion, detachment, migration, invasion and phosphorylation of downstream targets, including FAK, Akt a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Parental (MDA-MB-231) and brain metastatic cells (MDA-MB-231BR) do not exhibit differences in proliferation, although MDA-MB- 231BR showed a 2.5-fold increase in βIII-tubulin protein levels (47). Jiang et al (48) also demonstrated that targeting αv integrin with abitumumab inhibited prostate cancer cell adhesion, migration and invasion, but not proliferation in vitro . MicroRNA-124 inhibited hepatocarcinoma cell invasion and migration by suppressing αv integrin (49).…”
Section: Discussionmentioning
confidence: 98%
“…Parental (MDA-MB-231) and brain metastatic cells (MDA-MB-231BR) do not exhibit differences in proliferation, although MDA-MB- 231BR showed a 2.5-fold increase in βIII-tubulin protein levels (47). Jiang et al (48) also demonstrated that targeting αv integrin with abitumumab inhibited prostate cancer cell adhesion, migration and invasion, but not proliferation in vitro . MicroRNA-124 inhibited hepatocarcinoma cell invasion and migration by suppressing αv integrin (49).…”
Section: Discussionmentioning
confidence: 98%
“…Considered a good prognostic indicator, integrin ␣v␤ 6 is upregulated in various cancer types in inverse correlation with the patients' survival time (47). As of now, antagonists to integrin ␣v in the form of monoclonal antibodies have been successfully employed to halt melanoma and prostate cancer progression in vivo (48)(49)(50). Cilengitide, a cyclic RGD pentapeptide that selectively binds to and inhibits ␣v integrins, has even made it to phase III clinical trials (51).…”
Section: Discussionmentioning
confidence: 99%
“…d -pinitol downregulates αvβ3 integrin expression through two important pathways. First, this compound inhibits the FAK/c-Src kinase phosphorylation pathway, which plays an important role in cell motility and invasion in a dose-dependent manner [ 9 , 13 ]. Second, d -pinitol decreases p65 phosphorylation in the NF-κB signal transduction pathway [ 9 ].…”
Section: Natural Herbs Inhibit α2β1 and αVβ3 Integrinsmentioning
confidence: 99%
“…Integrins that contain the αv subunit contribute too many cellular functions that have been shown to promote malignancies, such as melanoma, renal cancer, colorectal cancer, and PCa [ 13 ]. Inhibition of αv integrin activation has been shown to reduce cell survival and induce cell cycle blockade [ 13 ]. This study also showed that this also reduced tumor growth and metastasis, thereby providing the desired antitumor effect.…”
Section: Monoclonal Antibodies Inhibit αV and β1 Integrinmentioning
confidence: 99%
See 1 more Smart Citation